The role of nectins in different types of cell–cell adhesion - Yoshiyuki Rikitake; Kenji Mandai; Yoshimi Takai (2012)
Summary Mammalian tissues and organs are composed of different types of cells that adhere to each other homotypically (i.e. interactions between cells of the same cell type) or heterotypically (i.e. interactions between different cell types), forming a variety of cellular patterns, including mosaic patterns. At least three types of cell–cell adhesion have been observed: symmetric homotypic, asymmetric homotypic and heterotypic cell adhesions. Cadherins and nectins, which are known cell–cell adhesion molecules, mediate these cell adhesions. Cadherins comprise a family of more than 100 members, but they are primarily involved in homophilic trans-interactions (i.e. interactions between the same cadherin members) between opposing cells. By contrast, the nectin family comprises only four members, and these proteins form both homophilic and heterophilic trans-interactions (i.e. interactions between the same and different nectin members on opposing cells). In addition, heterophilic trans-interactions between nectins are much stronger than homophilic trans-interactions. Because of these unique properties, nectins have crucial roles in asymmetric homotypic cell–cell adhesion at neuronal synapses and in various types of heterotypic cell–cell adhesions. We summarize recent progress in our understanding of the biology of nectins and discuss their roles in heterotypic cell–cell adhesions, whose formation cannot be solely explained by the action of cadherins.